1998
DOI: 10.1128/jvi.72.5.4038-4048.1998
|View full text |Cite
|
Sign up to set email alerts
|

The 30-Base-Pair Deletion in Chinese Variants of the Epstein-Barr Virus LMP1 Gene Is Not the Major Effector of Functional Differences between Variant LMP1 Genes in Human Lymphocytes

Abstract: One group of sequence variants of Epstein-Barr virus is characterized by a 10-amino-acid deletion within the CTAR-2 functional domain of the latent membrane protein, LMP1. A role for this deletion in enhancing the tumorigenicity of the viral oncogene in rodent fibroblasts was recently demonstrated. We examined the effect of this deletion upon LMP1 function in four human lymphoid cell lines by using three natural variants of LMP1: the prototype B95.8 gene and the CAO and AG876 genes, both of which have codons 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Our study has revealed consistent functional differences between the LMP1 variant derived from Hong Kong NPC and the prototype B95.8‐LMP1 isolated from B cells. A previous study comparing LMP1 isolates from different cellular origins also revealed differences in cell signaling activation 38. Our findings, along with other studies,6, 7 have demonstrated that the sequence differences of LMP1 isolates obtained from NPC cells could be translated into different functional phenotypes.…”
Section: Discussionsupporting
confidence: 80%
“…Our study has revealed consistent functional differences between the LMP1 variant derived from Hong Kong NPC and the prototype B95.8‐LMP1 isolated from B cells. A previous study comparing LMP1 isolates from different cellular origins also revealed differences in cell signaling activation 38. Our findings, along with other studies,6, 7 have demonstrated that the sequence differences of LMP1 isolates obtained from NPC cells could be translated into different functional phenotypes.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, lymphocytes natively transformed by EBV strains that have the aa 343-to-352 deletion mutant LMP1 are not more tumorigenic in nude or SCID mice, and the deletion has not been associated with poorer outcomes in EBV-associated human lymphoproliferative disease (3,17,18,62,63). Moreover, LMP1 with aa 343 to 352 deleted did not differ from wild-type LMP1 in NF-B activation or in induction of CD40 or CD54 surface expression on B-lymphoma cells (25,45). Thus, the overall significance of this deletion in the pathogenesis of EBV-related malignancies is uncertain.…”
Section: Discussionmentioning
confidence: 92%
“…52 NPCderived CAO-LMP1 is less cytostatic than B95-8 LMP1 ( Figure 5). 53 Such functional difference is attributed to amino acid differences in the transmembrane domain of LMP1, and is not related to the 30-bp deletion in the carboxy-terminal cytoplasmic domain. 53 Functional differences in LMP1 most likely contribute to differences in viral phenotypes, although this remains to be experimentally verified.…”
Section: Viral Latent Gene Heterogeneity and Deletions In Cancermentioning
confidence: 99%